A new tool for monitoring (child) poverty: measures of cumulative deprivation - Notten, Geranda; Roelen, Keetie (Université d'Ottawa | University of Ottawa, 2012)
Governments’ social indicator portfolios have expanded taking the multidimensionality of poverty into account. However, few if any, of the indicators provide insight into the degree to which persons experience several unfavourable conditions at the same time. This paper reviews and tests various indicators of cumulative deprivation that can be used to monitor child poverty and to identify vulnerable groups of children. This paper studies headcounts (counting deprived individuals) and adjusted headcounts (counting deprivations of deprived individuals) while the cumulative threshold can be distribution dependent (relative) or not (absolute). The measures are empirically tested on the 2007 EU-SILC data for the United Kingdom, Germany, France and the Netherlands. The findings indicate that the absolute adjusted headcount with a cumulative threshold of one deprivation is the most attractive candidate: it has an intuitive interpretation; it is sensitive to the breadth of deprivations but not oversensitive to changes in the methodology.
Keywords: poverty measurement; multidimensional poverty; material deprivation; cumulative deprivation; child poverty